Minimum income schemes in Europe: Is there a trade-off with activation policies? - Roberto Iacono (IZA Journal of European Labor Studies, 2017)
This paper makes two contributions to the literature. First, by employing a macro-level institutional dataset on benefit levels for social assistance (SA) and minimum income protection (MIP) in 22 European countries in the period 1990-2013, I show that the adequacy of income support for low-income inactive individuals in European welfare states has been steadily decreasing since 1994. Second, the paper revisits empirically the hypothesis of a trade-off between the adequacy of out-of-work benefits and the public expenditure on active labor market policies (ALMPs). The empirical results of the fixed effects model show that the trade-off does not appear to be significant in any of the tested specifications. The results are robust to the introduction of a set of conventional controls related to the labor market.
Keywords: H53; H55; I38; 330; Social assistance; Minimum income protection; Active labor market policies; European welfare states